Complete atrio-ventricular conduction block during complex partial seizure. - Wilder-Smith, E (1992)
Cardiac arrhythmias are a well known cause of epileptic seizures. Epileptic seizures resulting in cardiac arrhythmias are less well recognised and cardiac arrhythmias are commonly presumed to be of primary cardiac origin. This paper describes a patient with complete AV heart-block during a partial complex seizure. Simultaneous EEG/ECG monitoring was used to show the secondary nature of the bradyarrhythmia.